Решите уравнение: 0,6(у – 3) – 0,5(у – 1) = 1,5. 0,8(х – 2) – 0,7(х – 1) = 2,7.

Решите уравнение: 0,6(у – 3) – 0,5(у – 1) = 1,5. 0,8(х – 2) – 0,7(х – 1) = 2,7.
Гость
Ответ(ы) на вопрос:
Гость
 0,6(у – 3) – 0,5(у – 1) = 1,5 0,6у-1,8-0,5у+0,5=1,5 0,6у-0,5у=1,5+1,8-0,5 0,1у= 2,8 у=28                
Гость
Раскрываем скобки: Получаем 0.6y-1.8-0.5y+0.5=1.5 0.1y=1.5+1.8-0.5 0.1y=2.8 y=28 Ответ:y=28 Тоже самое : 0,8х - 1,6 - 0,7х + 0,7 = 2,7 0,8х - 0,7х = 2,7 + 1,6 - 0,7 0,1х = 3,6 х = 3,6 : 0,1 х= 36 Ответ x=36 Всё Незачто:)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы